Analisis Lingkungan Eksternal pada Faktor Faktor Kunci yang Perlu Diperhatikan - Mohamad Afrizal Miradji; Fitri Novita Putri Kirana; Nabilla Natcjwa Amanda; Nurul Fitrianingtyas; Tania Eka Sabrina (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
The external environment consists of various factors outside the organization that influence performance and the strategic decision-making process. These factors include economic, social, political, legal, technological and competitive aspects that continue to develop. Therefore, organizations need to analyze and understand the external environment in order to recognize opportunities that can be utilized and anticipate potential threats. Through a comprehensive analysis, organizations can formulate flexible and responsive strategies so that they are able to maintain sustainability and increase competitiveness in a changing market. This study aims to first certainly explain the concept of external environmental analysis, second to explain macro environmental factors through the PESTEL approach, third to explain the analysis of the industrial environment that includes aspects of competition and market power, fourth to compile an industrial competition profile through identifying competitor and market strengths, and fifth to predict business environmental conditions that can affect organizational strategy. The method used is a literature study with a qualitative descriptive approach. The results of the discussion show that external environmental analysis makes an important contribution to the preparation of adaptive, innovative, and sustainable business strategies.